Logics of Disintegration / Post-Structuralist Thought and the Claims of Critical Theory - Dews Peter (Verso, 1987)
The writer manages the exceptional feat of being both fair and clear in expounding Derrida, Lacan, Lyotard and Foucault. Preface and Acknowledgements, Introduction, Jacques Derrida: The Transcendental and Difference, Jacques Lacan: A Philosophical Rethinking of Freud, Jean-Francois Lyotard: From Perception to Desire, Michel Foucault: Power and Subjectivity, Michael Foucault: Power and Knowledge, Conclusion: Intersubjectivity and the Logic of Disintegration, Notes, Index.